Adult idiopathic communicating hydrocephalus with and without shunting. Issue 11 (November 1978) - Hughes, C P; Siegel, B A; Coxe, W S; Gado, M H; Grubb, R L; Coleman, R E; Berg, L
Abstract : The outcome in 37 adult patients with idiopathic communicating hydrocephalus treated by ventriculoatrial shunting is presented. Only 33% showed definite improvement, and no diagnostic procedures accurately predicted the outcome of surgery. These were compared with a "control" group of 12 patients who were not shunted; 50% of these were stable for up to 36 months. These findings, and the high frequency of serious complications (35%), suggest caution in recommending a shunt procedure.